2013
DOI: 10.3844/ajessp.2013.88.102
|View full text |Cite
|
Sign up to set email alerts
|

Drying Poultry Manure for Pollution Potential Reduction and Production of Organic Fertilizer

Abstract: Disposal and storage of raw poultry manure has become an environmental problem because of the associated air, water and soil pollution. Poultry manure begins to decompose immediately after excretion giving off ammonia which, in high concentrations, can have adverse effects on the health and productivity of birds as well as the health of the farm workers. Application to land is the most common way for utilizing poultry manure as a viable source of major plant nutrients and soil conditioner to improve soil tilth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Mosquera et al (2008) found that drying the poultry litter at 250 °C decreased the N content by 20 %. Ghaly and Alhattab (2013) also found losses of 35 % of the total N, with 42 % of this being from the ammonium form, after drying the poultry manure at 60 °C. For this reason, NH + 4 -N must always be determined in the poultry litter samples before drying.…”
Section: Resultsmentioning
confidence: 89%
“…Mosquera et al (2008) found that drying the poultry litter at 250 °C decreased the N content by 20 %. Ghaly and Alhattab (2013) also found losses of 35 % of the total N, with 42 % of this being from the ammonium form, after drying the poultry manure at 60 °C. For this reason, NH + 4 -N must always be determined in the poultry litter samples before drying.…”
Section: Resultsmentioning
confidence: 89%
“…The ammonia level was much higher in fresh chicken litter than in aged chicken litter (P Ͻ 0.05), as the initial high ammonia level (279.13 g NH 4 -N/g) in 0-month litter decreased to 56.37 g NH 4 -N/g in 9-month litter (Table 4). Generally, chicken litter, high in nitrogen content, begins to decompose immediately after excretion and releases ammonia in high concentrations (20). Chicken litter also gives off ammonia due to the production of ammonia from microbial mineralization of organic nitrogen compounds in the litter at the beginning of stockpiling (21).…”
Section: Resultsmentioning
confidence: 99%
“…The methods of agrobiological counts (the number of buds, shoots, buds on the bushes, accounting harvest berries from the bush and 1 hectare, and the average mass of clusters) were performed on establishing the vineyards on industrial scale (Ghaly and Alhattab, 2013).…”
Section: Objects and Methodsmentioning
confidence: 99%